CULTURAL MEMORY AND ITS INFLUENCE ON AUTOBIOGRAPHICAL MEMORY - Іванова, Олена Феліксівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
In this article the inﬂ uence of cultural memory on autobiographical memory is described on the basis of subjects’ recollections. The concepts of cultural and  autobiographical memory were analyzed, the data about early recollections, recollections of favorite toys, plays, books and animated cartoons are given. The conclusions about mediation of autobiographical memory by cultural artifacts, about reﬂ ection of traditional views about female gender role in the recollections were made. Cultural experience of the twenty-years old female generation is distinguished by the signiﬁ cant inﬂ uence of other cultures which is connected with new technological possibilities and social conditions.